http://www.online-rpd.org/journal/view.html?uid=42&sort=&scale=&key=year&keyword=&s_v=20&s_n=2&pn=vol&year=2014&vmd=Full - Shin-Chul Kim; Wang-Hyu Lee; Ju-Hee Kim; Kyu-Hwan Choi; Seong-Soo Cheong; Hong-Sik Shim (Research in Plant Disease, 2014)
This study was carried out to assay the disease incidence degree of Sclerotium rot caused by Sclerotium rolfsii in sixteen most popular commercial cultivars of sweet potato (Ipomoea batatas) in Republic of Korea. The degree of disease incidence was evaluated on pot experiments. In pot experiments using artificial inoculation, the Sclerotium rolfsii caused a stem rot on seedling of sweet potato plants and causes a crown rot on lower stems near or at the soil line at favorable environmental conditions. White mycelial mats and sclerotia were formed at the infection sites. Plants severely infected were fell over or died because lower stems near soil surface were rotten. The degree of disease incidence was varied according to cultivars. Two cultivars, Bio-mi and Deayumi, were very resistant, while five cultivars, Shinjami, Shingeonmi, Hongmi, Yeonjami, and Shinhung-3 were highly susceptible.